New insights in the taxonomy of Lepismatidae (Insecta, Zygentoma) with an updated key to genera and future challenges - Molero-Baltanás, Rafael; Gaju-Ricart, Miquel; Smith, Graeme B. (European Journal of Taxonomy, 2024)
This paper provides a revision of the morphological characters that can be used in the current taxonomy of Lepismatidae, and methodological guidelines for identification of silverfish, which requires the use of light microscope and can be helped by scanning electron microscopy. As a main objective, an updated key for the identification of all the genera of the world as they are established to date is provided and the incomplete knowledge of some of them is commented on. The insufficient knowledge of the diversity and geographic distribution of the six subfamilies of Lepismatidae is discussed, noting the most important shortcomings and problematic issues related to taxa belonging to this family, including the challenges for carrying out a comprehensive phylogeny of the group. Special attention is paid to the subfamily Ctenolepismatinae, the most diverse of Lepismatidae, erecting a new genus, Caribesella gen. nov., for the Caribbean species C. impudica comb. nov., which was previously included inside the genus Acrotelsella. We also consider that Sceletolepisma stat. nov. (i.e., sensu Irish 1987, including species with several median urosternal bristle-combs) deserves the status of a genus independent of Ctenolepisma, which, considered s. str. (i.e., lacking median urosternal combs), represents a heterogeneous group that requires further revision.